Longitudinal associations between Big Five personality and insomnia: evidence based on a 4-year perspective cohort study among community residents - Shao, Ziming; Wei, Zhen; Wang, Meiqi; Chen, Yifan; Qi, Yazhuo; Zhou, Zihan; Zhong, Yunxi; Qin, Afei; Xu, Yingyue; Wang, Kaixian; Wang, Wenyu; Sun, Long (Frontiers in Psychology, 2025)
IntroductionWhile the association between personality traits and insomnia has been confirmed, the longitudinal relationship between them remains unclear.MethodsThis is a 4-year longitudinal cohort study conducted among rural community residents (N = 482) in Shandong Province, China.ResultsThis study found that neuroticism (β = 0.175, p < 0.001), extraversion (β = −0.146, p < 0.001), and conscientiousness (β = −0.168, p < 0.001) at baseline had statistically significant longitudinal associations with insomnia at follow-up. In addition, insomnia at baseline had statistically significant longitudinal correlations with neuroticism (β = 0.142, p < 0.01), extraversion (β = −0.209, p < 0.001), and agreeableness (β = −0.122, p < 0.01) at follow-up.DiscussionThis study showed that both neuroticism and extraversion had a bidirectional relationship with insomnia. Insomnia had a one - way longitudinal correlation with agreeableness, and conscientiousness had a one - way longitudinal correlation with insomnia. The longitudinal correlation between openness and insomnia was not supported in this study.